Induction of Apoptotic Cell Death by Egg white combined-Chalcanthite on NCI-H460 Human Lung Cancer Cells - EunA Choi; Kyung-Hee Kim; Byong-Chul Yoo; Hwa-Seung Yoo (Korean Pharmacopuncture Institute, 2009)
Background : Anticancer effects of herbal medicine have been reported in various types of cancer, but the systematic approaches to explain molecular mechanism(s) are not established yet. Objective : The purpose of this study is to investigate the apoptotic cell death by Egg White combined Chalcanthite in NCI-H460 human lung cancer cells. Methods : Inhibitory effects were estimated by the MTT-assay. Cancer cells were stained with DAPI and showed condensed and fragmented nuclei. The expression of cleaved caspase-3, bcl-2, and bax was detected by western blotting. To establish a basis of understanding for anti-cancer mechanism, whole proteins have been obtained from NCI-H460 harvested at 24 hrs after the treatment of Egg White combined Chalcanthite, protein expression has been profiled by 2DE-based proteomic approach. Results : NCI-H460 human lung cancer cells were treated by three samples of IS3, IS4 and IS5. IS4 inhibited most effectively the growth of NCI-H460 human lung cancer cells. The expression of cleaved caspase-3 increased in IS4 in a concentration-dependent manner. Various changes of the protein expression have been monitored, and most frequent dysregulation was found in Vimentin, Lamin-A/C. Conclusion : Egg White combined-Chacanthite inhibited the growth of NCI-H460 human lung cancer cells by inducing the apoptotic cell death via caspase-3 activation. Based upon the present findings, the further study will focus on monitoring various cancer survival factors after artificial regulation of the proteins identified, and it would be the basis for the understanding of the Chacabthite anticancer effect(s) at the molecular level.